The Visual Light Field in Real Scenes. (December 2014) - Xia, Ling; Pont, Sylvia C.; Heynderickx, Ingrid
Human observers' ability to infer the light field in empty space is known as the "visual light field." While most relevant studies were performed using images on computer screens, we investigate the visual light field in a real scene by using a novel experimental setup. A "probe" and a scene were mixed optically using a semitransparent mirror. Twenty participants were asked to judge whether the probe fitted the scene with regard to the illumination intensity, direction, and diffuseness. Both smooth and rough probes were used to test whether observers use the additional cues for the illumination direction and diffuseness provided by the 3D texture over the rough probe. The results confirmed that observers are sensitive to the intensity, direction, and diffuseness of the illumination also in real scenes. For some lighting combinations on scene and probe, the awareness of a mismatch between the probe and scene was found to depend on which lighting condition was on the scene and which on the probe, which we called the "swap effect." For these cases, the observers judged the fit to be better if the average luminance of the visible parts of the probe was closer to the average luminance of the visible parts of the scene objects. The use of a rough instead of smooth probe was found to significantly improve observers' abilities to detect mismatches in lighting diffuseness and directions.